PENGARUH FEAR OF MISSING OUT (FoMO), HEDONIC SHOPPING LIFESTYLE, DAN VIRAL MARKETING TERHADAP IMPULSE BUYING PADA FLASH SALE PRODUK FASHION LAZADA (STUDI PADA GENERASI Z PENGGUNA LAZADA INDONESIA) - Vanissa Nada Risalah; Sari Listyorini; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2026)
Abstract: One of the impacts provided by social media is the existence of digital promotions that advance electronic commerce applications (e-commerce). In connection with the very tight competition in the e-commerce business in Indonesia, e-commerce applications innovate through the addition of features to attract consumer interest. One of the e-commerce that also innovates with attractive features such as Flash sales is Lazada. This study aims to determine the effect of Fear of Missing Out (FoMO), Hedonic Shopping Lifestyle, and Viral Marketing on Impulsive Buying at Flash Sale Lazada Fashion Products. This study uses explanatory research with a sample of 100 respondents and uses non-probability sampling techniques and purposive sampling research methods. The data was processed using the help of the SPSS version 26 program. The study shows the results that Fear of Missing Out (FoMO), Hedonic Shopping Lifestyle, and Viral Marketing have a significant positive effect on Impulsive Buying. Based on the test results, Lazada needs to increase Fear of Missing Out (FoMO), Hedonic Shopping Lifestyle, and Viral Marketing in supporting Impulsive Buying at the Lazada Fashion Product Flash Sale.Keyword: Fear of Missing Out (FoMO); Hedonic Shopping Lifestyle; Viral Marketing; Impulsive BuyingAbstrak: Salah satu dampak yang diberikan oleh media sosial adalah adanya promosi digital yang memajukan aplikasi perdagangan elektronik (e-commerce). Sehubungan dengan persaingan bisnis e-commerce yang sangat ketat di Indonesia, aplikasi e-commerce melakukan inovasi melalui penambahan fitur untuk menarik minat konsumen. Salah satu e-commerce yang juga berinovasi dengan fitur yang menarik seperti Flash sale adalah Lazada. Penelitian ini bertujuan untuk mengetahui pengaruh Fear of Missing Out (FoMO), Hedonic Shopping Lifestyle, dan Viral Marketing terhadap Impulsive Buying Pada Flash Sale Produk Fashion Lazada. Penelitian ini menggunakan explanatory research dengan sampel 100 responden serta menggunakan teknik non-probability sampling dan metode penelitian purposive sampling. Data diolah menggunakan bantuan program SPSS versi 26. Penelitian menunjukkan hasil bahwa Fear of Missing Out (FoMO), Hedonic Shopping Lifestyle, dan Viral Marketing berpengaruh positif signifikan terhadap Impulsive Buying. Berdasarkan hasil pengujian tersebut, Lazada perlu meningkatkan Fear of Missing Out (FoMO), Hedonic Shopping Lifestyle, dan Viral Marketing dalam menunjang Impulsive Buying Pada Flash Sale Produk Fashion Lazada.Kata Kunci: Fear of Missing Out (FoMO); Hedonic Shopping Lifestyle; Viral Marketing; Impulsive Buying